Sistem Kepercayaan, Sistem Nilai, dan Sikap Warga Kampus PENS Terhadap Mahasiswi Bercadar - Amarain Syahwa Zamalia; Albanoza Tamyda; Imamul Arifin (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2021)
This article describes  the social interactions  between residents of college students at the Electronic Engineering Polytechnic Institute of Surabaya (EEPIS)  on veiled female, including lecturers.Differences of belief, values, and attitudes in cultural pattern influences perception, especially the veil and Gamis clothes  are Arabic culture. It is dangerous for technical practice in Laboratium. Choosing students used purposive techniques with criteria as veiled college students of the EEPIS.The informants were 14 campus residents;  13 students and 1 lecturer. Data collection techniques  has used questionnaires about their beliefs, values, and Attitude on  veiled female college students in EEPIS. It found:1) four beliefs,2) four values, and various attitudes agree and  disagree on the veil female students  in EEPIS with their different arguments.